Conservation consortium for selected academic institutions with archives in Metro Manila - Laxamana, Emerald F.; Arlante, Salvacion M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2002)
The general objective of the study was to determine the possibility of establishing a conservation consortium among academic institutions with archives in Metro Manila. It aimed to: 1) describe and assess the facilities and resources available for conservation practices among the selected academic institutions with archives; 2) determine the willingness of the respondent institutions in participating and cooperating in conservation activities / programs; 3)Determine what benefits the individual respondent institutions could gain from conservation consortium; 4) Find out what services the individual institutions could render to the other participating members of the consortium. This study made use of the descriptive survey method. A structured questionnaire was the main instrument used to gather date. The respondents of the study were composed of six (6) academic institutions with archives in Metro Manila, namely: Ateneo de Manila University, Centro Escolar University, De La Salle University, University of the East, University of the Philippines Diliman and University of Santo Tomas.
Data gathered from this research were tallied, tabulated and analyzed. From the results of the study, it can be concluded that the establishment of conservation consortium for selected academic institution with archives in Metro Manila is possible because all the respondent institutions are willing to participate. This research study recommends the following: 1)development of a cooperative conservation program and proper implementation of policies to ensure the continuity of a conservation consortium; and 2) a treatment center be formed for the purpose of cost sharing in equipment as well as staff.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library cooperation -- Philippines -- Manila Metropolitan Area; Archives -- Philippines -- Manila Metropolitan Area